Gender-Based Violence Prevention in Schools in Myanmar:: A Study from Taunggyi - Soe Thiri Win; Buranajaroenkij, Duanghathai (Journal of Human Rights and Peace Studies, 2021)
Gender-Based Violence (GBV) in schools is a critical and pervasive issue in many countries, including Myanmar. There is persistent concern in preventing GBV and particularly in protecting women and girls. This article examines the understanding of GBV among primary school teachers and the extent of GBV prevention in schools. This research examines forms of GBV occurring in Basic Education High schools in Taunggyi and explores teachers’ responses to GBV in schools from a human rights perspective. For this study 19 educators and a GBV expert were interviewed using in-depth interviews as well as focus group discussions held in two schools. The findings suggest that in order to prevent GBV it is necessary to improve the awareness and knowledge of GBV in schools, not only to ensure students’ safety in school and the surrounding environment but also to equip students with awareness of GBV by integrating it into the school curriculum. It is necessary to improve responses to GBV at the primary school level in terms of policy, activity programmes and curriculum, since schools can play an important role in cultivating a culture of human rights and awareness to prevent GBV which could gradually become embedded in the community and society.